Target-directed proteolysis at the ribosome - Henrichs, Tanja (National Academy of Sciences, 2005)
Target directed proteolysis allows specific processing of proteins in vivo. This method uses tobacco etch virus (TEV) NIa protease that recognizes a seven-residue consensus sequence. Because of its specificity, proteins engineered to contain a cleavage site are proteolysed, whereas other proteins remain unaffected. Therefore, this approach can be used to study the structure and function of target proteins in their natural environment within living cells. One application is the conditional inactivation of essential proteins, which is based on the concept that a target containing a recognition site can be inactivated by coexpressed TEV protease. We have previously identified one site in the secretion factor SecA that tolerated a TEV protease site insert. Coexpression of TEV protease in the cytoplasm led to incomplete cleavage and a mild secretion defect. To improve the efficiency of proteolysis, TEV protease was attached to the ribosome. We show here that cleaving SecA under these conditions is one way of increasing the efficiency of target directed proteolysis. The implications of recruiting novel biological activities to ribosomes are discussed.